Research and application of the key techniques of postoperative comprehensive management of autologous arteriovenous internal fistula - HUANG Jian-fang; SHI Yu; TANG Xiang-chun; PENG Hong-mei (Linchuang shenzangbing zazhi)
Objective To explore the application effect of the key techniques of comprehensive management in patients with end-stage renal disease(ESRD)at the under-maturity stage after autologous arteriovenous internal fistulation(AVF).Methods The patients were randomly divided into control group and experimental group.In both groups,oral explanation and exercise demonstration were used to train the grip function after the surgery,and all the patients used EH101 electronic grip apparatus.On this basis,the key techniques of comprehensive management were implemented in the experimental group,and remote follow-up management was conducted.Results At weeks 4,8 and 12,the measured diameter values of blood vessels in the experimental group were greater than those in the control group,and the blood flow was higher than that in the control group(P<0.05).The rate of fistula maturity rate 3 months after operation in the experimental group was higher than that in the control group(P<0.05).Grip strength exercise compliance in the experimental group was higher than that in the control group(P<0.05).Conclusions The key techniques of comprehensive management can effectively promote the maturation of autologous arteriovenous internal fistula and improve the compliance of patients with functional exercise.